The empirical empire : Spanish colonial rule and the politics of knowledge - Brendecke, Arndt (De Gruyter Oldenbourg, 2016)
How was Spain able to govern its enormous colonial territories?In 1573 the king decreed that his councilors should acquire "complete knowledge" about the empire they were running from out of Madrid, and he initiated an impressive program for the systematic collection of empirical knowledge.